Die hermeneutische Wendung im Frühwerk Martin Heideggers - Großheim, Michael (Bollettino Filosofico, 2020)
The hermeneutical turn is a methodological innovation in Heidegger’s thought. This innovation is pursued in Heidegger’s lectures from 1919 on; it reaches its peak in § 32 of “Being and Time”. The main point of the hermeneutical turn consists in a twofold critique: 1) a critique of the distanced intuition of essence (“Wesensschau”) and various kinds of objectifying attitudes prevailing in philosophy in a way not sufficiently reflected upon. It is here where hermeneutics should have its proper domain as it consists in man’s self-interpretation and in the interpretation of their situation. 2) a critique of traditional hermeneutics’ focus on texts which underexposes the point that human life itself is primordially hermeneutical. The result is an original though to date not yet sufficiently received contribution to phenomenology regarding the question of how to find the way “to the things themselves”. In this respect, Heidegger can be considered as a pioneer of “epistemological explicationism” (Hermann Schmitz). Keywords: Explication, Fore-Conception, Hermeneutics, Interpretation, Situations